PELINDUNGAN HUKUM PENCIPTA TERHADAP PERWUJUDAN HAK CIPTA - Hasibuan, Dinda Yayuk Wahyu; Saidin, Ok; Azwar, T. Keizerina Devi (Smart Education, 2025)
Abstract: The lawsuit filed by the creator regarding the protection of computer program writings related to online motorcycle taxi ordering/order-on-demand services occurred because the creator believed that their economic and moral rights had been violated and commercially exploited without permission or knowledge. The issues raised in this study include: (1) How creators’ rights over copyright claims are recognized; (2) How ownership of unregistered copyrighted works is proven; and (3) Why the Supreme Court Decision No. 1033K/Pdt.Sus-HKI/2023 did not recognize anyone as the creator of the computer program writings concerning online motorcycle taxi ordering/order-on-demand services.Keyword: Legal Protection, Creator, Copyright Materialization, Computer Program Abstrak: Gugatan pencipta terhadap pelindungan karya tulis program komputer mengenai cara pemesanan ojek online/order on demand services, terjadi karena pencipta merasa hak ekonomi dan hak moralnya sebagai pencipta atas suatu karya cipta telah dilanggar dan dimanfaatkan secara komersial, tanpa izin dan tanpa sepengetahuannya sebagai pencipta, yaitu: 1) Bagaimana hak pencipta atas klaim terhadap perwujudan hak cipta; 2) Bagaiamana pembuktian kepemilikan hak cipta terhadap hasil ciptaan yang tidak didaftarkan; dan 3) Mengapa di dalam Putusan Mahkamah Agung Nomor 1033K/Pdt.Sus-HKI/2023 tidak ada yang dianggap sebagai pencipta atas karya tulis program komputer mengenai cara pemesanan ojek online/order on demand services.Kata kunci: Pelindungan Hukum, Pencipta, Perwujudan Hak Cipta, Program Komputer